Between nature and culture – Interpreting students’ sexuality in physical education - Böhlke, Nicola; Zander, Benjamin; Rode, Daniel (Frontiers in Sociology, 2024)
Introduction As sexuality in physical education (PE) is often treated as a taboo subject, social media platforms, online chats, and internet forums are emerging as spaces where it is negotiated more openly and broadly by current and former actors of the field. This paper contributes to a better understanding of the discursive construction of sexuality in PE in such online communication. Methods In line with The Sociology of Knowledge Approach to Discourse (SKAD) we investigate basic schemes of interpretation of sexuality with a heterogeneous sample of threads (17 threads from seven different online forums) on different PE situations in Germany. The threads are analyzed using grounded theory coding procedures. Results Our discourse analysis reveals that the multifaceted and often controversial online discussions are structured by two dominant schemes of interpreting students’ sexuality in PE, both of which are differentiated in complex ways: The online communication draws on – and by that reproduces – a nature and a culture perspective on constellations of body, sex, gender, and sexuality. We detail how from each perspective, different knowledge about these constellations, different everyday phenomena and problems in PE, and different norms for dealing with these phenomena and problems become important. Discussion Discussing these results in the context of previous literature, we argue that it is important to address sexuality in a subject-specific approach and take the discursive knowledge and fundamental schemes of interpretation into account that shape the (im-)possibilities of addressing sexuality in PE.